Inflammatory response to different endodontic irrigating solutions - Tanomaru, M.; Leonardo, M. R.; Silva, LAB; Anibal, F. F.; Faccioli, L. H. (Blackwell Publishing, 2002)
Aim the aim of this study was to evaluate the inflammatory response to irrigating solutions injected into the peritoneal cavity of mice.Methodology Sixty mice received intra-peritoneal injections of 0.3 mL of 0.5% sodium hypochlorite, 2.0% chlorhexidine digluconate or phosphate buffered saline (PBS, control). Five animals of each group were sacrificed at 4, 24, 48 h and 7 days after the injection. Liquid from the peritoneal cavity of each animal was collected for the total and differential counting of inflammatory cells and protein leakage.Results the 0.5% sodium hypochlorite solution group had greater migration of neutrophils and mononuclear cells to the peritoneal cavity from 48 to 168 h (P < 0.05). There was a significant increase in protein leakage to the peritoneal cavity after 4 up to 48 h in the 0.5% sodium hypochlorite group compared to the control group. Protein leakage was similar in all groups at 168 h. The 2.0% chlorhexidine group had similar results to the control group at all time periods.Conclusions the 0.5% sodium hypochlorite solution induced an inflammatory response, however, the 2.0% chlorhexidine digluconate solution did not induce a significant inflammatory response.
Keywords: biocompatibility; chlorhexidine; endodontic irrigating solutions; inflammation